Procedures In The English Translation Of Stylistic Devices Commonly Used In “Lục Xì” By Vũ Trọng Phụng - Nguyễn Thị Thu Nga (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Stylistics and stylistic devices, for a long time, have been considered the fundamental factor in creating the beauty of any literary works. There are many different kinds of stylistic devices and each kind of them brings different effects. This thesis is carried out to investigate the stylistic devices commonly used in the reportage “Lục Xì” by Vũ Trọng Phụng and their English translational equivalents in “Luc Xi: Prostitution and Venereal Disease in Colonial Hanoi” by Shaun Kingsley Malarney to discover the translation procedures in translating these Vietnamese stylistic devices into English version. On the basis of translation procedures by Peter Newmark, we realized that stylistic devices have strong effects on these two works and the translation methods which are used to render stylistic devices make their meanings change in some ways. This thesis focused on simile, irony and metaphor – the three most typical stylistic devices which were used commonly and distinctively in literary work as well as identify different procedures which the translator applied to convert these stylistic devices into English, including literal translation, expansion, reduction, couplet, transposition, and naturalization for similes; literal translation, cultural equivalent, transposition, reduction, couplet, expansion, and transference for metaphors; and literal translation, transposition, reduction, synonymy, couplet, cultural equivalent, and expansion for irony. Finally, based on the findings and results of this study, some implications have been proposed to contribute to teaching and learning English as a foreign language. Moreover, the awareness of learners in using stylistic devices for interpreting literary works will also be suggested.